The therapeutic efficacy and safety of traditional Chinese medicine injection combined with low-molecular-weight heparin on the acute lower extremity deep venous thrombosis: A protocol for systematic review and network meta-analysis. Issue 50 (17th December 2021) - Zeng, Mulan; Liao, Qian; Cui, Yinjie; Tang, Hongbo; Yu, Maowen
Abstract: Background: Lower extremity deep venous thrombosis (LEDVT) of lower extremities is one of the common clinical diseases. Lack of a timely treatment in the acute stage easily causes pulmonary embolism, thus seriously threatening patients' life. Low-molecular-weight heparin (LMWH), as a new generation of heparin-based anticoagulant and antithrombotic drug, is now commonly used in the clinical treatment of acute lower extremity deep venous thrombosis (ALEDVT). Relevant randomized controlled trials (RCTs) have reported the therapeutic efficacy and safety of Traditional Chinese medicine injection (TCMJ) combined with LMWH on ALDVT, although their conclusions remain controversial. In addition, the efficacy of various TCMJs has rarely been analyzed and compared. This study aims to evaluate the therapeutic efficacy and safety of TCMJ combined with LMWH on ALEDVT through a network meta-analysis. Methods: RCTs reporting TCMJ combined with LMWH and LMWH along for the treatment of ALEDVT published before November 2021 will be searched in online databases, including the Cochrane Library, Embase, PubMed, Web of Science, Wanfang, Chongqing VIP Chinese Science and Technology Periodical Database, Chinese Biomedical Literature Database, and Chinese National Knowledge Infrastructure. Two investigators will be independently responsible for literature screening, data extraction, and quality evaluation according to Cochrane's risk of bias assessment tool. R software will be used to perform a network Meta-analysis. Results: The results of this meta-analysis will be submitted to a peer-reviewed journal for publication. Conclusion: This study will provide high-quality, evidence-based medical evidence for comparing the therapeutic efficacy and safety of TCMJ combined with LMWH and LMWH alone on ALEDVT.